Peran Teknologi Dalam Mengembangkan Potensi Ekspor Topeng Malangan (Analisis Situasional Dan Rencana Solusi) - Finahari, Nurida (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
The art of chisel mask is developed in Tumpang Malang area as part of dance costume fairs, puppet show andcultural ritual, although in its development, this mask sculpture is also sold and become a tourism commodity. The potentialsales of mask sculptures is increasing, especially because of the demanders are foreign tourists, cultural enthusiasts andcomponent of tourism activities. That is, Topeng Malangan has the potential to be developed as an export commodity. Thesales system is still limited to cultural events or when there is a visit of education and tourism to the arts-padepokan. Thisprompted some people around the padepokan to start a home industry to meet the availability of the mask. In general, theproblems encountered by the craftsmen are (1) availability of raw materials, especially for suitable wood species, (2)production equipment, especially for pre-carving process and preservation of product, (3) there is no standard marketingscheme, (4) does not have a business management system, and (5) highly skilled craftsmen are still very limited. The solutionsoffered are divided into three stages: (1) technological strengthening, including strengthening production process technologyand increasing the number of craftsmen; (2) establishing business management; and (3) establishing trademarks, copyrightsand product marketing expansions